Driving job satisfaction through inclusive knowledge management: a focus on learning and communication in diverse workplaces - Sobia Naseem; Muhammad Mohsin; Khalid Jamil (BMC Psychology)
Abstract Background This study examines the impact of knowledge management practices (KMP) on job satisfaction, focusing on the mediating roles of learning opportunities and communication quality. It aims to provide insights into how effectively KMP can enhance employee satisfaction in Pakistan's IT sector. Method The research utilizes cross-sectional data collected from 345 IT sector employees in Pakistan. A survey method was employed, using a structured questionnaire to gather the necessary data. The data was then analyzed to determine the relationships between KMP, learning opportunities, communication quality, and job satisfaction. Results The findings reveal that KMP has a significant positive impact on job satisfaction. Additionally, KMPs are found to positively influence learning opportunities and communication quality, which in turn significantly contribute to job satisfaction. The results demonstrate that learning opportunities and communication quality mediate the relationship between KMP and job satisfaction. Discussion This study recommends that the IT sector in Pakistan can improve job satisfaction by developing effective KMP that supports learning and communication quality. These practices also enhance employee satisfaction and are compatible with the identified strategic objectives of a knowledge-based economy in Pakistan's framework. In addition, this research extends the theoretical literature on the relationship between KMP and job satisfaction, with learning opportunities and communication quality as mediating factors. It offers important implications for IT firms and presents a foundation for future studies to examine potential moderators and replicate these results in other industries and geographies.